2019
DOI: 10.1007/s10964-019-01095-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Family Correlates of Intrinsic Religiosity Profiles Among Low-Income Urban African American Adolescents

Abstract: National trends show that African American adolescents, relative to most other demographic groups, are more religious, and show fewer declines in religiosity, despite drastic decreases in religiosity among youth over the past 25 years. These broad findings are limiting because they fail to acknowledge religious heterogeneity among African American teens. Further, there are few empirical investigations of the transmission of religiosity within African American families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…It would also be instructive for future research with more sample diversity to consider whether changes in religious doubt may have a stronger impact on health marginalized youth groups based on sex and race, as these groups already display declines in religiosity during emerging adulthood (Kliewer et al. 2020; Woodell and Schwadel 2020)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would also be instructive for future research with more sample diversity to consider whether changes in religious doubt may have a stronger impact on health marginalized youth groups based on sex and race, as these groups already display declines in religiosity during emerging adulthood (Kliewer et al. 2020; Woodell and Schwadel 2020)…”
Section: Discussionmentioning
confidence: 99%
“…Although there are multiple religious pathways that young people can follow, emerging adults are more likely to decrease their attendance at religious services (Barry and Abo‐Zena 2014; Uecker, Regnerus, and Vaaler 2007), consider religious disaffiliation (Sherkat and Wilson 1995; Smith 2000; Vargas 2012) and become less religious on other dimensions, such as subjective religious importance, spiritual connectedness, or prayer frequency (Fisher 2017; Kliewer et al. 2020; Simsek et al. 2019; Smith and Snell 2009; Uecker et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, they used existing data focused more generally on the emotional climate of the parent–adolescent relationship (indexed via the Children's Report of Parent Behavior [CRPBI]) to test James's (2016) conceptualization of microprotections. Although the Parental Acceptance Subscale of the CRPBI is a widely used measure of parental warmth and support, it tends to assess how reflective the items are of the caregiver (e.g., really unlike or really like ) rather than the frequency of the behaviors (Gonzalez et al, 2021; Kliewer et al, 2020), and some have reported poor test–retest reliability (intraclass correlation coefficient = .47; Gonzalez et al, 2021). Building on this work, the present study developed a scale to index the small daily caring, supportive, and loving behaviors parents engage in and extended past research by testing the generalizability of parental microprotections beyond Black adolescents and their families.…”
Section: Supportive Parenting In the Context Of Discriminationmentioning
confidence: 99%
“…An important role in this process is played by the extent to which parents discuss, argue and give reasons about why certain things are moral or not, and how a decision can affect others (Hoffman 1970; Cornwall 1989; Regnerus 2003; Petts 2015). Even if adolescents develop their autonomy as they age, parents still exert a great influence on them, especially in the development of values (Kliewer et al 2019).…”
Section: Introductionmentioning
confidence: 99%